THE ROLE OF PHOTOGRAPHY AS A MEDIA FOR PRESERVATION OF BALI ANCIENT SCRIPTS - Dinata, Ramanda Dimas Surya; Wijaya, Putu Sinar; Andani, Dea (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2022)
ABSTRACT Efforts to save ancient Balinese manuscripts have been attempted since 1928 through the establishment of a special lontar library. Over time, the lontar library began to be seen as less effective in inventorying and in terms of publishing ancient manuscripts. This problem is the reason why ancient manuscripts need to be made an inventory in the form of digitization. Visually digitizing photography is able to give a real picture both in terms of form, message, and elements of the ejection object. Observation and interview methods were used as a research flow and as a practical process in the field. The realization of research related to the digitization of lontar is divided into three stages, namely pre-production (pre-shooting), production (shooting) and post-production (post-shooting). The results of the study show that first, photographic digitization of lontar can be useful for science on a global scale and can be an inventory of Balinese cultural wealth. Second, it is useful to digitally introduce the history of Balinese civilization and provide actual and reliable information. Third, helping the classification process related to the contents of the lontar, the origin of the lontar, and the physical condition of the lontar. Fourth, it makes it easier to do lontar research which can be done anywhere. Fifth, digitizing photography is able to maintain and avoid damage to ancient manuscripts (lontar) as a cultural heritage of a region. Keywords: lontar, digitization, photography, Bali